Humanising entrepreneurship development programme for youth in Afghanistan - Asrar, Mohammadullah; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2019)
The highest rate of unemployment among youth has drawn everyone’s attention globally. This trend is at its increasing pace in many developing countries and people are seeking to find a solid solution. According to the SDG4 goal of Quality Education, education systems should be optimised where universities and colleges nurture knowledgeable, skilled and ethical graduates especially entrepreneurs in order to help in creating decent job opportunities for their own selves and creating job opportunities for others. Therefore, the aim of this paper is to propose conceptualise Youth Entrepreneurship Development Programme model where youths can develop and harness their entrepreneurial knowledge and skills with human values. In addition to entrepreneurship-based education, this conceptual paper is to help youth in creating start-up ventures and small and medium sized enterprises (SMEs) that result in economic transformation of society, creating more decent job opportunities, and enhancing societal well-being. This paper adapted the design thinking methodology providing business models, plans and strategies to humanise entrepreneurship education programme. The main contribution of this paper is a conceptual business model to empower youths through humanising entrepreneurship education in Afghanistan to nurture their entrepreneurial, knowledge, skills and Islamic values in creating job opportunities.